Exploring the influence of organisational culture on women's perceptions of gender diversity, equity, and inclusion initiatives in the manufacturing sector - Kinnear, Lisa (University of Pretoria, 2025)
Mini Dissertation (MBA)--University of Pretoria, 2024.